1992
DOI: 10.1021/ma00047a028
|View full text |Cite
|
Sign up to set email alerts
|

Anionic polyamides modified with poly(oxypropylene) by "one-shot" RIM technology: structural and morphological characterization

Abstract: Anionic nylon 6 modified with poly(oxypropylene) up to 40% by weight and obtained by one-shot reaction injection molding ("one-shot" RIM) was characterized by wide-angle X-ray diffraction, transmission electron microscopy, differential scanning calorimetry, thermal gravimetric analysis, and Fourier transform infrared spectroscopy. Cross analysis by different techniques pointed out that the polymer contained only the a-form and the modifier had little, if any, influence on the crystallinity index, which was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 3 publications
(5 reference statements)
1
23
0
Order By: Relevance
“…[40] It can be seen that for all the MCPA6/ABS samples there were double peaks appearing at 2y of about 20.18 and 23.68, which correspond to the crystallographic planes (200) and (002þ202) of the a-form crystal of the MCPA6 component. [41][42][43][44] Figure 9 shows that both peaks corresponding to the crystals of MCPA6 components remained at almost the same position, despite the varying composition. After heat treatment of the samples at 80 8C and 120 8C, there was little change, and no other crystal form was present (see Figure 10).…”
Section: Thermal Propertiesmentioning
confidence: 94%
“…[40] It can be seen that for all the MCPA6/ABS samples there were double peaks appearing at 2y of about 20.18 and 23.68, which correspond to the crystallographic planes (200) and (002þ202) of the a-form crystal of the MCPA6 component. [41][42][43][44] Figure 9 shows that both peaks corresponding to the crystals of MCPA6 components remained at almost the same position, despite the varying composition. After heat treatment of the samples at 80 8C and 120 8C, there was little change, and no other crystal form was present (see Figure 10).…”
Section: Thermal Propertiesmentioning
confidence: 94%
“…16 A similar morphology has been observed in other polyamide-polyether copolymers and blends. 15,17,18 The polyamide domains in Figure 1 were estimated to be about 20 -50 nm compared with 2 nm for the individual nucleated ␤-sheets, suggesting that the ␤-sheets aggregated in some fashion in the solid state. At higher magnification (inset, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Boscoletto et al observed interpenetrating phases in nylon-6/poly(oxypropylene) blend. 18 No overall orientation or lamella morphology is apparent in Figure 1, possibly because the film was an unsheared solvent-cast one. Our attempts to generate oriented fibers and films have so far resulted in formation of brittle material with low mechanical strength.…”
Section: Methodsmentioning
confidence: 99%
“…Many efforts have been made to try and improve the impact resistance of PA 6. For example, reactive elastomeric compounds have been incorporated, [1][2][3][4][5][6][7][8][9][10][11] such as amine-or hydroxy-terminated elastomers (which are usually modified by diisocyanate or blocked by dicaprolactam), into e-caprolactam by in situ polymerization to form composites. Because of the poor miscibility of the elastomer and the PA 6 matrix, large rubbery domains form, leading to inferior ultimate properties of the composite.…”
Section: Introductionmentioning
confidence: 99%